Physico-Chemical Characteristics of Ganga River Water at Two Selected Sites within Haridwar City, Uttarakhand: A Comparative Study - Aditi, (International Journal of Psychosocial Rehabilitation, 2017)
This study is focused on the physico-chemical parameters of the Ganga River water during the year 2016. Water samples were collected monthly from two selected sites viz. Sapta Rishi Ghat and Har ki Pauri. During the present study, physicochemical parameters were monitored with the help of standard methods of APHA and Trivedi & Goel. Selected physicochemical parameters such as temperature, total Solids (TS), total dissolved solids (TDS), total suspended solids (TSS), turbidity, transparency, pH, dissolved oxygen (DO), Bio-chemical oxygen demand, total hardness, and chlorides were analyzed. It was found that anthropogenic activities were responsible for water quality degradation in the Ganga River.